Helicobacter pylori Genotyping and Sequencing Using Paraffin-Embedded Biopsies from Residents of Colombian Areas with Contrasting Gastric Cancer Risks - Sicinschi, Liviu A. (2008)
BACKGROUND: cagA-positive and vacA s1 and m1 genotypes of Helicobacter pylori are associated with an elevated risk of gastric cancer (GC). We determined these genotypes using paraffin-embedded gastric biopsy specimens harvested from infected individuals and compared genotype distributions in two Colombian populations residing in geographic regions with a high and low incidence of GC. METHODS: DNA from paraffin-embedded gastric biopsies from 107 adults was amplified using primers specific for cagA, for the cag ‘empty site’, for the s and m alleles of vacA, and for H. pylori 16S rRNA. RESULTS: H. pylori infection was detected by molecular assays in 97 (90.7%) biopsies. Complete genotyping of cagA and vacA was achieved in 94 (96.9%) cases. The presence of cagA was detected in 78 of 97 cases (80.4%); when considered separately, cagA and vacA s regions were not significantly associated with a particular geographic area. The vacA m1 allele and s1m1 genotypes were more common in the area of high risk for GC (p = .037 and p = .044, respectively), while the vacA m2 allele and s2m2 genotypes were more prevalent in the low-risk area. The prevalence of the combination of cagA-positive, vacA s1m1 genotypes was 84.3% and 60.5% for high and low risk areas, respectively (p = .011). CONCLUSIONS: H. pylori cagA and vacA genotyping from paraffin-embedded gastric biopsies permitted reliable typability and discrimination. The more virulent cagA-positive s1m1 strains, as well as vacA m1 genotype, were more prevalent in high risk than in low risk areas, which may contribute to the difference in GC risk between those two regions.